The Development of a Family Support Program for Caregivers of Hemodialysis Patients - Mercado, Myrna A. (STIKes Patria Husada Blitar, 2024)
Family caregivers of hemodialysis patients have a heavy burden based on negative experiences, long-term care hours, total physical dependence of patients, comorbid health conditions, and financial stress treatment procedures. This study design is a mixed method followed by 114 participants in the quantitative phase and eight participants in the qualitative phase. The research instrument used Zarit Burden, a demographic profile form, semi-structured interview questions, and a recorder. Data analysis used ANOVA, t-test, and thematic analysis. The results showed that most participants were 51 to 60 years old, patients' wives, college graduates, had a monthly income below ph10,000.00 and had cared for patients for 20 to 24 hours. Participants have experienced high physical and financial burdens and loss of control over life, as well as very high emotional and social burdens. Significant differences were found in the levels of emotional, social, and financial burdens when grouped by education level. Monthly income affects the level of social and financial burdens. Physical exhaustion, emotional suffering, limited social life, role conflict, financial poverty, and fear of the future are the themes of challenges in caregiving. Participants coped with their challenges by seeking help and sleep, emotional adjustment, acceptance, maintaining friendships, resisting the urge to participate in social activities, utilizing family resources, seeking financial support from politicians and government agencies, and borrowing money. The proposed stress relief support program has the potential to be an intervention to enable family care with various forms and levels of caregiving burden.